Modulation of Tsallis entropy and corresponding thermodynamic properties of impurity doped GaAs quantum dot in presence of noise - Bhaskar Bhakti; Swarnab Datta; Manas Ghosh (Next Nanotechnology)
Present inspection minutely explores the features of Tsallis entropy and the corresponding internal energy and heat capacity of GaAs quantum dot (QD) incorporating Gaussian impurity. Simultaneous influence of Gaussian white noise (GWHN) has also been invoked where GWHN enters the system by means of additive and multiplicative modes. The study unfolds extremely subtle interplay between temperature, entropy index, GWHN, mode of incorporation of GWHN and the particular physical parameters concerned. The resultant influence of the said interplay finally governs the traits of the Tsallis entropy-based thermal properties. The investigation manifests competitive behavior between thermal disorder and spatial disorder that prominently affects the thermal properties.